Fluoxetine Improves Motor Function in Patients with Severe Motor Deficit When Given Early after Ischemic Stroke - Vinall, Maria (MD Conference Express, 2011)
The Multicenter Randomized Double-Blind Placebo-Controlled Trial with Fluoxetine on Motor Rehabilitation After Acute Ischemic Stroke [FLAME; NCT00657163] trial, showed that the early use of fluoxetine in addition to physiotherapy in patients with severe motor deficit resulting from ischemic stroke enhances motor recovery after 3 months.